1990
DOI: 10.1139/v90-266
|View full text |Cite
|
Sign up to set email alerts
|

Acidities and homolytic bond dissociation energies of the αC—H bonds in ketones in DMSO

Abstract: Can. J. Chem. 68, 1714 (1990). Equilibrium acidities in DMSO are reported for nine cycloalkanones, acetone, acetophenone, and 19 of their a-substituted derivatives. Oxidation potentials in DMSO for the conjugate bases of most of these ketones are also reported. Combination of these Eox(A-) and pKHA values gives estimates of the homolytic bond dissociation energies (BDEs) of the acidic C-H bonds in the ketones. The ABDEs, relative to the BDE of CH3-H, or a parent ketone, provide a measure of the radical stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 7 publications
5
60
1
Order By: Relevance
“…1 and for the reduction of 1 (p-= 13.0 * 1. all cases. While most of these redox reactions are irreversible (Table l), Bordwell et al (9)(10)(11)(12) have shown that for a series of structurally related species, the changes in redox properties closely approximate thermodynamic changes; i. e., tammetry) also have been shown to be close to EO (16,17,21).…”
Section: Ch3mentioning
confidence: 98%
See 2 more Smart Citations
“…1 and for the reduction of 1 (p-= 13.0 * 1. all cases. While most of these redox reactions are irreversible (Table l), Bordwell et al (9)(10)(11)(12) have shown that for a series of structurally related species, the changes in redox properties closely approximate thermodynamic changes; i. e., tammetry) also have been shown to be close to EO (16,17,21).…”
Section: Ch3mentioning
confidence: 98%
“…Recently, Arnold and co-workers (6-8) and Bordwell et al (9)(10)(11)(12) used this approach for the determination of pK,'s of radical cations and (or) the energies for the homolytic cleavage of C-H bonds. More recently, Arnett et al (1 3-15) combined calorimetric and electrochemical measurements to obtain data for the heterolytic C-C cleavage reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of C26-H of desmosterol and Z-but-2-ene, the inductive effect of geminal alkyl group diminishes the stabilizing mesomeric effect of double bond and results in the higher BDE value of the sterol. (Bordwell 1990). …”
Section: Calculation Of Bdesmentioning
confidence: 99%
“…This course is in fact not unexpected, since even the prototype nucleophilic glucopyranosyl radical, generated from acetobromoglucose, [17] produces the hydrogen transfer product 1,5-anhydroglucose tetraacetate in a yield of over 20% on reaction with acrylonitrile, [17b] and the 2-oxoglycosyl radical 8 is clearly less nucleophilic, if not essentially electrophilic due to its push-pull Ϫ or capto-dative [18] Ϫ substitution: an electron-withdrawing group such as a carbonyl moiety next to a carbon radical entails a stabilization by some 10Ϫ12 kcal/mol in relation to a ''pure'' C-radical, [19] and the additional presence of a cycloalkoxy group allows for a variety of mesomeric forms (i.e., 8a o 8b o 8c, Scheme 3). This is likely to result in a planar arrangement of O5ϪC1ϪC2ϪC3 (i.e., a 4 H 5 half chair form rather than a mere 4 C 1 -type chair geometry as in 8a).…”
Section: Radical C-glycosidationmentioning
confidence: 99%